Kompetensi Pedagogik Guru Pendidikan Agama Islam - Maya Puspita Sari; Masykur Mansyur; Abdul Kosim (Universitas Muhammadiyah Jember, 2021)
The presence of an instructor is crucial figure in training particular skills. Educators are experts whose duties are to teach, educate, guide, direct, survey, and assess students in the field of youth development, formal schooling, essential and elective teaching (UU RI Number 14 of 2005 concerning Educators and Teachers). Competent educators must have skills, where the ability of the instructor has 4 kinds of abilities. First, character abilities, educational skills, proficiencies and social skills. The Effect of Educational Capability of PAI Instructors on Learning Income uses a quantitative plan by polling. The sample used in this study amounted to 160 students consisting of 4 classes. The variable of the Educational Capability of the PAI Instructor was estimated through a poll survey of Variable X using research instruments and the Premium Variable in Learning was estimated through a survey of variable Y with 10 items each from each factor. To examine the need for investigations though testing the regularity of information by using instructive factual tests in the flagship program. Then, the investigation using the Sperman Rank Connection synopsis was carried out. To find out the consequences of speculative testing, it can be seen that there is a relationship between the learning model of PAI Educators' Educational Ability and student learning income. In the Sperman Rank Connection table, the ends are: The theory being tried is recognized whether the t value is calculated in the t table. Based on the estimation results above, it shows that t count = 7.5 t table 1.9916. This implies that there is a relationship between the Academic Ability of PAI Educators and Student Income in Learning